Comprehensive sedimentological and sequence stratigraphic ‎characterization of the exposed Boka Bil Formation, Surma ‎Basin, Northeastern Bangladesh - Md. Abdur Rahman; Md. Shafiqul Alam (International Journal of Advanced Geosciences, 2025)
The Surma Basin, situated in northeastern Bangladesh along the northeastern margin of the ‎Indian subcontinent, is a region characterized by tectonic activity. This study investigates the ‎Miocene siliciclastic sedimentary succession exposed at the Hari River section in Lalakhal, ‎Jaintiapur, to explore its depositional environments and sequence stratigraphic architecture. ‎Field observations and sedimentological analysis reveal two primary facies associations within ‎the Boka Bil Formation: FA1 (tide-dominated environments) and FA2 (shelf environments). ‎FA1 includes three facies: Facies A (tidal channel deposits), Facies B (alternating sandstone and ‎mudstone representing overbank deposits), and Facies C (distal overbank deposits), which ‎together depict a lateral transition from tidal channel margins to spillover deposits. FA2 consists ‎of Facies SL1 (inner shelf deposits) and Facies SL2 (outer shelf deposits), representing deeper ‎marine environments. The Boka Bil Formation displays a retrogradational stacking pattern, with ‎a fining-upward sequence that transitions from shallow to deeper marine conditions. This ‎pattern is indicative of a transgressive systems tract, driven by rising sea levels. The deepening-‎upward facies succession highlights the dynamic interplay between tectonic forces and sea-level ‎changes in an active margin setting. These findings enhance our understanding of sedimentary ‎processes, paleoenvironmental evolution, and regional stratigraphy, providing valuable insights ‎for resource exploration in tectonically influenced basins‎.